O USO DO MÉTODO DE SUPERFÍCIE DE RESPOSTA NA OTIMIZAÇÃO TERMOECONÔMICA DE SUPERESTRUTURAS MODELADAS EM SOFTWARE COMERCIAL PARA PROJETO DE SISTEMAS DE RECUPERAÇÃO DE CALOR RESIDUAL EM MOTORES DIESEL ESTACIONÁRIOS - Araujo, Leonardo Rodrigues de (2020)
In a world with finite resources of natural fuels, increased energy demand and increasing levels of environmental pollution, issues related to the thermal systems design, such as energy efficiency, cost estimation, design complexity, environmental awarene